Gendered community : Rousseau, sex, and politics - Weiss, Penny A. (New York University Press, 1993)
"Rousseau's writings reflect paradoxes and apparent inconsistencies with his principled commitments to freedom and equality. In this engrossing work, Penny Weiss wrestles with issues of gender in the works of Rousseau. Weiss attempts to resolve apparent inconsistencies by placing them within the context of Rousseau's political philosophy, while avoiding the impulse to attribute his remarks on the sexes to the sexist times in which he wrote, or to his personal idiosyncracies. A significant contribution to feminist theory, this book addresses the debates concerning Rousseau's understandings of gender, justice, freedom, community, and equality. She also examines how Rousseau's political strategies give rise to a range of important contemporary questions regarding families, citizens, and communities. This new, more complete picture of Rousseau's work will challenge scholars and students of philosophy, politics, and women's studies to look at, and understand, Rousseau in a whole new way. Penny A. Weiss addresses the apparent male/female contradictions that run through the work of the eighteenth-century philosopher Jean-Jacques Rousseau. She argues that Rousseau's defense of sexual differentiation is based on the contribution he perceives it can make to the establishment of community, not on an appeal to some version of natural sex differences. Weiss convincingly demonstrates that Rousseau's political strategy is ultimately unworkable, undermining the very community it was meant to establish."--EBSCO